The competency niche: An exploratory study - Zbysław Dobrowolski; Grzegorz Drozdowski; Jósef Ledzianowski (Risks, 2021)
In the era of a turbulent and less-predictable business environment, as confirmed by the COVID-19 pandemic, the ability to efficiently use human resources has become particularly important. There is a need to reduce employees' competency niche, and competency mismatches have become noticeable in the European Union. We performed qualitative interviews (n = 282) to determine the competency niche of employees from private firms in Poland. Results show that employees were passive in identifying their competence needs. Moreover, firms did not use the weak signals methodology to eliminate the competency niche. This novel study found that firms should be more active in identifying employee competency niches by analyzing early signs to be ready for any changes without delays. The findings create a basis for proposing preventive measures, and we point out avenues for future research.
Keywords: 330; competencies; weak signals; foresight; agile; business and management